Penerapan Model Cooperative tipe NHT dengan Wordwall: Solusi Inovatif Pembelajaran Ekonomi - Rahmatilah, Leni; Sadiah, Ati; Solihat, Ai Nur (SJEE (Scientific Journals of Economic Education), 2026)
This study aims to determine the effectiveness of the Number Head Together (NHT) learning model assisted by wordwall media on student learning outcomes in Economics class XI at SMAN 10 Tasikmalaya. The study used an experimental research method with a quantitative approach using a Non-Equivalent Control Group Design. The sampling technique used a non-probability sample with purposive sampling. The sample consisted of 70 students, with 35 students in the experimental class and 35 students in the control class. The results showed an N-Gain of 2.25, with an average posttest score of 81.68 for the experimental class and 67.69 for the control class. The significance value (p-value) was < 0.001 and < 0.05, indicating that the NHT cooperative learning model assisted by wordwall had a significant effect and provided maximum improvement in learning outcomes.